A densely-sampled Sanger-based phylogeny of the temperate Gondwanan family Triaenonychidae (Opiliones: Laniatores), inferred from three markers - Baker, Caitlin M. (2019)
The armoured harvestman family Triaenonychidae (Opiliones: Laniatores) has a predominantly temperate Gondwanan distribution, with representatives in southern South America, South Africa, Madagascar, Australia, New Zealand, New Caledonia, and one genus in eastern North America. Despite being one of the most diverse families of harvestmen with ca. 477 described species and subspecies, they have received little systematic attention until recently, and no phylogeny focusing on this family, molecular or morphological, has been published. Herein, we present a molecular phylogeny of Triaenonychidae inferred from three markers (18S rRNA, 28S rRNA, and COI), representing all the geographic areas from which they are known, and including over 300 terminals spanning ~60% of described genera. We demonstrate that nearly all the landmasses from which triaenonychids are found contain nonmonophyletic assemblages, and while most recognised genera are monophyletic, some, including the diverse trans-oceanic genus Nuncia, as well as the New Zealand genera Karamea and Triregia, are poly- or paraphyletic and require taxonomic revision. Our phylogeny also rejects the monophyly of all four currently accepted subfamilies (Triaenonychinae, Triaenobuninae, Adaeinae, and Sorensenellinae), and calls into question the familial rank of the New Zealand-endemic Synthetonychiidae. Despite limited nodal support along the backbone of the phylogeny, we recover an apparent division between taxa from Eastern Gondwana (Australia, New Zealand, New Caledonia) and Western Gondwana (South America, Africa).